Detection of Haemophilus ducreyi from environmental and animal samples in Cameroon. - Philippe Ndzomo; Serges Tchatchouang; Onana Boyomo; Tania Crucitti; Michael Marks; Sara Eyangoh (PLoS Neglected Tropical Diseases)
Background Children in parts of Africa, the South Pacific, and Southeast Asia frequently develop cutaneous ulcers caused by two bacteria: Haemophilus ducreyi (HD) and Treponema pallidum subspecies pertenue (causative agent of yaws). The World Health Organization (WHO) aims to eradicate yaws using mass administration of azithromycin. This also leads to a temporary decrease in ulcers caused by HD followed by a rebound suggesting an ongoing reservoir of infection. The aim of this study was to investigate whether HD could spread through the environment or animals. Methods Alongside detection of human cases of cutaneous ulcers from villages in Cameroon, we additionally collected samples from animals (dogs, cats, flies), fomites (bedsheets, clothing, benches, doors), and water sources (marigots and lakes). DNA was extracted and tested for HD and T. pallidum using two specific qPCR assays. Results HD was not detected in any of the environmental samples but it was on both clothing (13.3%) and in flies (27%). Flies also tested positive for T. pallidum, but at a lower rate (2.6%). Conclusions These results suggest that flies and some fomites may contribute to the transmission of HD. Future research should focus on determining whether either of these are capable of carrying live bacteria that can cause onward transmission.